ARRANGEMENT OF LIBRARIES AND TRAINING OF VOCATIONAL SCHOOL LIBRARIANS IN SINGARAJA CITY IMPLEMENTING SLIMS ASSISTED DIGITAL LIBRARIES - putu yana wardana (ACARYA PUSTAKA, 2021)
The rapid development of information technology has an impact on various fields of life and profession, this has led to system changes in institutions including libraries. The use of information technology in the world of libraries must be carried out considering the rapid flow of information and the large amount of data (big data) has undergone very rapid changes. Along with the rate of development of information technology that has touched all levels of society. Libraries play a role as a force in the preservation and dissemination of scientific information, a reference place for seekers of knowledge and the development of scientific works. With the application of information technology in libraries, nowadays it has become a measure to determine the level of progress of the library, no longer the size of the building used, the number of bookshelves or the crowds of books. SLIMS is a solution in implementing digital-based libraries so as to maximize the services and libraries of SMK. To overcome the above, vocational school services were held by conducting librarian training and library arrangement using the SLIMS application which was carried out virtually during the Covid pandemic. Of the three target schools, Vocational High Schools throughout Singaraja city all sent two librarian representatives each to take part in virtual zoom-based training, besides that, it was also attended by undiksha librarians, students and lecturers in the scope of the library study program. Furthermore, an MOU has been held in collaboration with the school and d3 libraries in library management and training for librarians to apply SLIMS-based digital libraries.Keyword : Training; Librarian; Structuring; Digital library; SLIMS